Two Small Extracellular Vesicle sRNAs Derived From Mycobacterium tuberculosis Serve as Diagnostic Biomarkers for Active Pulmonary Tuberculosis - Lu, Geng; Jiang, XinRui; Wu, Anni; Zhou, Jiawei; Liu, Hengjun; He, Fei; Zhang, Qiuling; Zen, Ke; Gu, Shuangshuang; Wang, Jun (Frontiers in Microbiology, 2021)
The rapid diagnosis of tuberculosis (TB) is of great significance for the control and treatment of TB. However, TB remains a major healthy, social, and economic burden worldwide because of the lack of ideal diagnostic biomarkers. Mycobacterium tuberculosis (M. tuberculosis)-encoded small RNA (sRNA) is a class of regulation small RNA. Several studies have identified M. tuberculosis encoded-sRNAs in the serum/plasm of M. tuberculosis-infected patients. Small extracellular vesicles are small membrane vesicles secreted by many cell types during physiological and pathological conditions. Recent evidence has indicated that most of the nucleic acids in the serum/plasma are packaged in the small extracellular vesicles and could serve as ideal diagnostic biomarkers. In this study, we attempted a novel approach for TB diagnosis: targeting small extracellular vesicles M. tuberculosis encoded sRNA (sRNA) by qRT-PCR. The results showed that M. tuberculosis-encoded ASdes and MTB-miR5 only existed in tuberculosis patients and have the potential to serve as a sensitive and accurate methodology for TB diagnosis.